Pengengaruh Teknik 3M Terhadap Kemampuan Menulis Teks Berita Siswa Fase F SMA Negeri 1 Cijaku - Wiliyanti, Wiliyanti (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to determine the effect of 3M techniques on class XI students of SMA Negeri 1 Cijaku. This research was conducted based on the problem of the low ability to write news texts in high school students, which is characterized by students having difficulty in working on questions that are different from those modeled by their teachers. This research aims to determine the difference in the influence of the writing ability of students who learn using the 3M technique and students who use the Outline technique. The method in this research uses quantitative methods. The population and sample in this research were class XI students of SMA Negeri 1 Cijaku in 2 classes selected randomly or Random Sampling. The instrument used in this research was a news text writing ability test. The test used is a question type test. Based on the results of data analysis, the results of this research concluded: There is a difference in the influence of the ability to write news texts on students who learn using the 3M technique and students who learn using the Outline technique. The ability to write news texts for students who learn the 3M technique is better than students who learn using the Outline technique. This can be seen from the results of the hypothesis test, namely using the Independent Samples Test, which obtained a sig value of 0.021 < 0.05, meaning it shows that the variance between groups is not the same. So it can be concluded that there is a significant difference in the increase in the influence of the 3M technique on the ability to write news texts for high school students.